Analisis Kualitas Produk dan Layanan Sebagai Strategi Membangun Daya Tarik Konsumen pada Resto Pondok Ghobyos di Karangrejo, Kabupaten Banyuwangi - Syifa Setiawan; Avan Wicaksono; Febi Wulandari; Afifatul Fiqriyah; Elok Rosyidah (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study aims to analyze product quality and service quality as strategies to build consumer attraction at Resto Pondok Ghobyos in Karangrejo, Banyuwangi Regency. The subject of this study is Resto Pondok Ghobyos, which applies a concept of preparing food fresh with fresh ingredients as well as services that prioritize friendliness and a family-like atmosphere. The study uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews with the owner, direct observation of the restaurant's operational processes, and other supporting documentation. The results of the study show that product quality is implemented through the selection of fresh ingredients daily, a processing method done directly without storage, and consistency in flavor, which is the restaurant's distinctive characteristic. The quality of service is reflected in the friendliness of the owners and employees, the speed of service, personal attention, and the family-like atmosphere built with customers. Research findings show that the combination of consistent product quality and humanized service quality can create consumer appeal, increase the interest to visit, and generate positive experiences that encourage customer loyalty. Thus, product and service quality become the main